2022
DOI: 10.26676/jevtm.v6i1.234
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative Thoracotomy and Aortic Cross-Clamp and Resuscitative Endovascular Balloon Occlusion of the Aorta

Abstract: There are three methods of aortic occlusion; RTACC (resuscitative thoracotomy with aortic cross-clamp), abdominal aortic compression/occlusion after laparotomy, and REBOA. It is essential to understand the characteristics of each methods and use them appropriately according to the situation or in combination. RTACC is characterized by its rapidity and certainty, but highly invasive. Abdominal aortic compression/occlusion is beneficial because hemostasis after laparotomy can be performed simultaneusly. Advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Harmonizing patient selection criteria for REBOA in trauma management An analysis of 10 recent studies of REBOA in trauma patients describing patient selection criteria found that most described similar criteria (Table 1) [3,[18][19][20][21][22][23][24][25][26]. A pivotal criterion uniformly identified across these articles is the manifestation of hypotension, characterized by a transient or insufficient response to resuscitative interventions.…”
Section: Main Textmentioning
confidence: 99%
“…Harmonizing patient selection criteria for REBOA in trauma management An analysis of 10 recent studies of REBOA in trauma patients describing patient selection criteria found that most described similar criteria (Table 1) [3,[18][19][20][21][22][23][24][25][26]. A pivotal criterion uniformly identified across these articles is the manifestation of hypotension, characterized by a transient or insufficient response to resuscitative interventions.…”
Section: Main Textmentioning
confidence: 99%